A Cross-sectional Study of Rosacea and Risk Factors in Women with Frontal Fibrosing Alopecia - María Librada Porriño-Bustamante; María Antonia Fernández-Pugnaire; Salvador Arias-Santiago (Medical Journals Sweden, 2019)
Frontal fibrosing alopecia has been related to some autoimmune diseases, but the association with rosacea is not clear. The objective of this study was to analyse the prevalence of rosacea in a group of patients with frontal fibrosing alopecia. A cross-sectional study, including 99 women with frontal fibrosing alopecia and 40 controls, was performed, in which clinical, dermoscopic and hormonal data were analysed. Women with frontal fibrosing alopecia presented a higher prevalence of rosacea than the controls did (61.6% vs. 30%, p = 0.001), especially those with severe grades of alopecia (77.8% in grade V vs. 33.3% in grade I, p = 0.02). Binary logistic multivariate analysis showed that perifollicular erythema (odds ratio (OR) 8.5; 95% confidence interval (95% CI) 1.73-42.30), higher body mass index (OR 1.16; 95% CI 1.01-1.34) and lower progesterone levels (OR 0.15; 95% CI 0.028-0.89) were associated with a higher risk of rosacea in patients with frontal fibrosing alopecia. In conclusion, patients with frontal fibrosing alopecia presented a higher prevalence of rosacea than did controls. Perifollicular erythema, higher body mass index and lower progesterone levels were associated with a higher risk of rosacea in the group with frontal fibrosing alopecia.